Agama dan kepercayaan di dalam masyarakat majemuk di Indonesia - Prasetyaningsih, Dwi (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2024)
Humans and religious are two things that cannot be separated because the process of human search for God or the Creator of the heavens and earth is trough rituals and then becomes a religion which becomes a label of certain belief. The more developed human civilization develops and the more complex the procedures for human life, both social culture, language and society. That things the also has an influence on the way human seek God. The more modifications and ways of performing rituals, the more religions and beliefs appear. Humans have their own understanding and of the religion or belief the believe in. Like wise Christians how can they remain firm and uphold the truth in the midst of diversity. And all pack religion and belief with their own goodness and truth.